The production of Bahlā Ware in the context of late Islamic Oman - Živković, Jelena; Carvajal Lopez, Jose; Döpper, Stephanie; Biezeveld, Irini (Proceedings of the Seminar for Arabian Studies, 2025)
Among glazed Arabian Gulf wares, Bahlā Ware stands out as one of the most documented objects of consumption at sites in Oman, the UAE, Qatar, and Bahrain from the sixteenth to the early twentieth century. Previous scientific studies of Bahlā Ware from UAE and Qatar formed the basis for understanding its production technology and provenance, as well as the unique composition of its lead-barium glaze. This paper presents the new results of petrographic and chemical analyses of thirty-two Bahlā samples from Oman, contributing to a better understanding of the compositional variability of ceramics, the provenance of raw materials, and techniques used for the application of lead-barium glazes. The compositional match between samples of Bahlā Ware from Oman, the UAE, and Qatar reveals the exploitation of the same geological source of raw materials over several centuries. Previous research has associated this source with the ophiolitic geological formation in Oman. The results of chemical analysis of glazes confirmed that the Omani samples were also coated with a lead-barium glaze of the same type as reported for UAE and Qatar.